Penerapan Metode Inner Product Pada Aplikasi E-Diagnosa Agranulositosis - Enrio Situmeang (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
An expert system (expert system) is a system that seeks to adopt human knowledge to computers, so that computers can solve problems like experts. The large number of people affected by orthopedic disease and the lack of orthopedic specialists make it difficult for orthopedic specialists to handle a large number of patients. One way to solve this problem is to create an expert system for diagnosing orthopedic diseases. Orthopedic disease diagnosis expert systems can help experts as reliable assistants with the aim of helping patients to continue to receive treatment even though experts are not available. This expert system can certainly solve a problem about Otopaedics by imitating the workings of an Orthopedic specialist. The inner product method is used for initial diagnosis by inputting the patient's symptoms. The result of the inner product process is taken as the highest value as the output in the form of the name of the disease and the type of patient treatment. If the highest value generated from the inner product process is more than one and the symptoms of the disease have a quantity and time value, it will proceed to further diagnosis using the certainty factor method, by inputting the length of time for each symptom, or the quantity of symptoms to determine the value of confidence in a particular symptom. disease based on the duration of each symptom and the quantity of these symptoms.